Carpal Tunnel Syndrome as a Complication of Surgical Scaphoid Reconstruction in Nonunion and Secondary Fracture Dislocation - Brackertz, Sophie; Andronic, Octavian; Reissner, Lisa; Pastor, Torsten; Schweizer, Andreas; Nagy, Ladislav (Journal of Wrist Surgery, 2023)
The purpose of this study was to identify risk factors for postoperative carpal tunnel syndrome (CTS) in operative management for scaphoid nonunion and secondary fracture dislocation, treated surgically with takedown and bone grafting. We reviewed medical records of all our patients that underwent carpal tunnel release after scaphoid reconstruction surgery from August 2002 to December 2020. We identified a total of 7 out of 191 patients (3.7%). We investigated surgical parameters, pre- to postoperative changes, in three-dimensional measurements of the scaphoid and carpal tunnel morphometry. We found the preoperative intrascaphoid angle (ISA) and the postoperative change in ISA to correlate with an increased risk of postoperative CTS. Patients undergoing operative scaphoid reconstruction that require a high degree of geometric correction can be at risk to develop postoperative CTS, hence they should be subject to a lower threshold decision for prophylactic carpal tunnel release.Level of Evidence Level III.
Keywords: scaphoid reconstruction; postoperative carpal tunnel syndrome; pseudarthrosis; complication carpal reconstruction; CARD analysis